New evidence of relative age effects in "super-elite" sportsmen: a case for the survival and evolution of the fittest - Jones, B. D.; Lawrence, G. P.; Hardy, L. (Journal of Sports Sciences, 2018)
The relative age effect (RAE) describes an overrepresentation of players born early (Q1) in a selection year and is highly prevalent within youth sport pathways. However, a dearth of research has investigated the RAE at the "super-elite" level. The present research assessed the presence of RAE in super-elite performers. Study 1 investigated RAEs in the world`s best international Test cricketers (N = 262) over a 20-year period according to a robust and stringent "super-elite" criteria. Results revealed the RAE (Q1) when all disciplines were combined. Upon closer examination, this effect was also observed for the batting and spin bowling disciplines, whereas no RAE was found for the pace bowling discipline. Study 2 investigated RAEs in super-elite rugby union players (N = 691) over a 20 year period. Results revealed the RAE for backs (Q1) and a reversal of the traditional RAE (Q4) for forwards, and when all rugby union positions were combined. These findings provide new evidence of RAEs at the super-elite level and present both inter and intra sports differences. Potential explanations for these findings are explored, owing to the survival and evolution of the fittest concepts, and the implications for future research and applied practice are presented.